Weakly nonlinear ion sound waves in gravitational systems - Guio, P; Pécseli, H L (Physical review. E, 2020)
Ion sound waves are studied in a plasma subject to gravitational field giving rise to vertically inhomogeneous steady-state plasma conditions. Such systems are interesting by exhibiting a wave growth that is a result of energy flux conservation for pulses propagating in an inhomogeneous system. The increase of the amplitude of a pulse as it propagates along the density gradient in the direction of decreasing density gives rise to an enhanced interaction between waves and plasma particles that can be modeled by a modified Korteweg-de Vries equation. Analytical results are compared with numerical particle-in-cell simulations of the problem. Our code assumes isothermally Boltzmann distributed electrons resulting in a nonlinear Poisson equation. The ion component is treated as a collection of individual particles interacting through collective electric fields. Deviations from quasineutrality are allowed for.